Pregnancy with Maternal Caroli’s Disease - Case Report - Meenakshi T Sahu; Chitranshu Vashishtha; Anuradha; Shruti (Journal of Women's Reproductive Health, 2015)
A maternal case of Caroli’s disease in pregnancy is described, with attention to diagnostic imaging, obstetric management, and maternal–fetal risks.
Keywords: Caroli's disease